An Analysis of the Statistics Content in Nepali School Textbooks (Mathematics Education Forum Chitwan, 2019)
To determine the nature and extent of the statistics content that Nepali students may learn in school, we examined mathematics textbooks for grades 4-10 from five different publishers. All of the tasks in each statistics chapter were examined, for a total of 1755 tasks across 35 textbooks. Each task was classified according to the phases of the statistical problem-solving process (formulate questions, collect data, analyse data, interpret results) that were addressed. Nearly every task required students to analyse data; the other phases were rarely addressed. Additionally, tasks addressing the analysis phase were coded according to analysis activities; the majority of these tasks required students to read a display and perform a mathematical calculation. For each series, at least two-thirds of the statistics tasks followed a similar worked example. Based on these findings, we offer recommendations for teachers, text book writers, and the Curriculum Development Centre.